2014
DOI: 10.1103/physrevb.89.220504
|View full text |Cite
|
Sign up to set email alerts
|

Time-reversal-invariant topological superconductivity induced by repulsive interactions in quantum wires

Abstract: We consider a model for a one-dimensional quantum wire with Rashba spin-orbit coupling and repulsive interactions, proximity coupled to a conventional s-wave superconductor. Using a combination of Hartree-Fock and density matrix renormalization group calculations, we show that for sufficiently strong interactions in the wire, a time-reversal invariant topological superconducting phase can be stabilized in the absence of an external magnetic field. This phase supports two zeroenergy Majorana bound states at eac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
128
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(129 citation statements)
references
References 46 publications
0
128
0
1
Order By: Relevance
“…It has been well demonstrated that the class DIII topological invariant can take a nontrivial value only if there exist at least two bands with opposite sign of the pairing potential [38,40,41,50,61], or, equivalently, that the anomalous component of the self-energy has both positive and negative eigenvalues. It was also shown in Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well demonstrated that the class DIII topological invariant can take a nontrivial value only if there exist at least two bands with opposite sign of the pairing potential [38,40,41,50,61], or, equivalently, that the anomalous component of the self-energy has both positive and negative eigenvalues. It was also shown in Ref.…”
mentioning
confidence: 99%
“…In one dimension (1D), where superconductivity is required to be induced by the proximity effect, it has been shown that a nontrivial topological phase in class DIII can be realized by proximity coupling a noninteracting multichannel Rashba nanowire to an unconventional superconductor [36][37][38][39] or to two conventional superconductors forming a Josephson junction with a phase difference of π [40]. Alternatively, an effective π -phase difference can be induced in a multichannel Rashba nanowire with repulsive electron-electron interactions [41] or in a system of two topological insulators coupled to a conventional superconductor via a magnetic insulator [42]. It has also been proposed to realize class DIII topological superconductivity in a system of two Rashba nanowires [43][44][45] or two topological insulators [46] coupled to a single conventional superconductor, but repulsive interactions are also necessary to reach the topological phase in these setups, which require a strength of induced crossed Andreev (interwire) pairing exceeding that of the direct (intrawire) pairing [47][48][49].…”
mentioning
confidence: 99%
“…Hence the admissible solutions decay as exp(−|∆ 0 | r ⊥ ) in the bulk, where i z = i ∆ 0 can be identified with the EP solution with complex k ⊥ . In 1d, numerous lattice models have been studied which can support one [22] or multiple MBSs [27][28][29][30][31][32] at one edge of an open chain. For such models, one can show that the chiral MBS solutions at an edge, obtained by the transfer matrix approach formalism [22,[27][28][29]33] in the lattice space, have the same relation with the EP solutions obtained in the complex k-space.…”
mentioning
confidence: 99%
“…The criterion exploits the behavior of the ground state energy of a system of N, and N AE 1 particles, for both periodic and antiperiodic boundary conditions. The emergence of topological order in a superconducting wire, closed in a ring and described in mean field, is associated [6,[39][40][41][42][43][44]. Any spin-active superconductor, topologically trivial or not, may experience a crossing of the ground state energies for even and odd number of electrons [45][46][47][48].…”
mentioning
confidence: 99%